2017
DOI: 10.1093/gerona/glx163
|View full text |Cite
|
Sign up to set email alerts
|

Relationships of Clinical and Computed Tomography-Imaged Adiposity with Cognition in Middle-Aged and Older African Americans

Abstract: WC may be the simplest and most efficient measure of adiposity to assess with respect to cognition in clinical settings, although studies to determine mechanistic effects of subcutaneous and other adiposity depots on cognition are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 41 publications
1
3
0
Order By: Relevance
“…In addition, measures of adiposity and their relationship with cognition may differ by adiposity depot. 9 However, the assessment of the association between WC categories and cognitive function showed that high WC potentially attenuates declines in cognition, similar to our results using BMI. Although we excluded underweight participants and participants aged 65 years and older in sensitivity analyses, we did not examine whether weight loss was associated with attrition from the study and thus cannot completely rule out reverse causation or attrition bias as partly contributing to the paradoxical association of BMI and cognitive decline.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In addition, measures of adiposity and their relationship with cognition may differ by adiposity depot. 9 However, the assessment of the association between WC categories and cognitive function showed that high WC potentially attenuates declines in cognition, similar to our results using BMI. Although we excluded underweight participants and participants aged 65 years and older in sensitivity analyses, we did not examine whether weight loss was associated with attrition from the study and thus cannot completely rule out reverse causation or attrition bias as partly contributing to the paradoxical association of BMI and cognitive decline.…”
Section: Discussionsupporting
confidence: 88%
“…Some studies show no association or a mildly increased risk between midlife obesity and CID and no or decreased risk of late-life obesity with CID, likely due to the prodromal weight loss phenomenon that occurs up to 10 years before dementia diagnosis. [7][8][9][10] Less is known about differences in the relationship between obesity and CID in Black and White adults, and longitudinal studies with racial diversity are particularly sparse. Studies have found that the effect of vascular risk factors on the brain might differ between Black and White adults.…”
mentioning
confidence: 99%
“…3 Higher BMI has been associated with lower dementia risk in older age, likely due to the pre-clinical weight loss phenomenon that occurs prior to a dementia diagnosis. 4 However, waist circumference relationships to cognition are stronger in older age compared to body mass index (BMI), are more consistently associated with dementia risk across age than BMI, 5,6 and, compared to BMI, waist circumference is considered a more valid measure of obesity in older adults. 7 Obesity is more common in African American than White individuals 8 and may contribute to the disproportionate burden of dementia in African American individuals.…”
Section: Introductionmentioning
confidence: 99%
“…Some cross-sectional studies showed that high-VFA individuals had a significantly higher prevalence of MCI [20,21]. However, others have shown that there is no significant association between VFA and MCI [22] or cognitive function [23]. Furthermore, a recent study of more than 5000 Japanese individuals showed that visceral fat accumulation was protective against MCI [24].…”
Section: Introductionmentioning
confidence: 99%